Pengaruh Pengaruh Budaya, Komitmen Organisasi dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan - Rensi Apriani; Venny Puspita; Janusi Waliamin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Employee performance is one of the benchmarks in a company's efforts to achieve its goals. One of the determining factors for the success of employee performance is Organizational Citizenship Behavior (OCB). This study aims to determine how much influence organizational culture, organizational commitment, and Organizational Citizenship Behavior (OCB) have on the performance of employees of PT. Matahari Department Store Bengkulu. This research is included in the type of explanatory research that uses quantitative methods to explain the influence of organizational culture variables (X1), organizational commitment (X2), organizational citizenship behavior (X3) and employee performance (Y) as well as to test the hypotheses that have been formulated. The population in this study are all employees of PT. Matahari Department Store Bengkulu, totaling 43 people. The method of analysis is carried out qualitatively and quantitatively by conducting validity tests, reliability tests and econometric tests. The results showed that organizational culture variables had an effect on performance, while organizational commitment and organizational citizenship behavior had no effect on performance. as a whole there is an influence of organizational culture, organizational commitment and organizational citizenship behavior on employee performance at PT. Matahari Department Store Bengkulu.